THE EFFECT OF PERFORMANCE MEASUREMENT SYSTEM IMPLEMENTATION ON THE JAMBI LOCAL GOVERNMENT PERFORMANCE - Muhammad Gowon; Fortunasari Fortunasari; Yusnaini Yusnaini (AKUNTABILITAS, 2020)
The purpose of this study is to investigate the effect of the implementation factors of Performance Measurement System (PMS) on government institution to the organizational performance of the Regional Device Work Unit (RDWU). Implementation, use and accountability are the stages of activity undertaken in the design of performance measurement systems. While the performance of the organization is the achievement of management as measured from the level of achievement of the program plan determined by the realization of the program that has been determined. Performance is measured by using a financial and non-financial approach whose data comes from the financial bureau and the regional organization bureau of Jambi province. The respondents of this study are 52 civil servants who are mostly part of the program staff. The type of data used is primary and secondary data from over 50 RDWU Jambi. This study is based on Quantitative Method of Structural Equation Modeling method using Partial Least Square (WarpPLS 6.00) analysis to test the hypothesis built. There is evidence that management commitment and leadership style have a significant positive effect on the use of PMS information. Legislative Council Authority and Supervision of Supreme Audit Board (SAB) also have a significant effect on performance accountability. This research has theoretical implication that institutional isomorphism occurs in everyday practice in the field and it plays an important role in the implementation process of performance measurement and accountability system in the public sector, especially in government of Jambi province. From the policy-making perspective, this research can be considered by the central government, legislative council and SAB that internal and external performance measurement system has a positive effect on the use of PMS and performance accountability in the provincial government of Jambi.